Pentavalent HIV-1 vaccine protects against simian-human immunodeficiency virus challenge - Bradley, Todd; Pollara, Justin; Santra, Sampa; Vandergrift, Nathan; Pittala, Srivamshi; Bailey-Kellogg, Chris; Shen, Xiaoying; Parks, Robert; Goodman, Derrick; Eaton, Amanda; Balachandran, Harikrishnan; Mach, Linh V.; et al. (Nature communications, 2017)
The RV144 Thai trial HIV-1 vaccine of recombinant poxvirus (ALVAC) and recombinant HIV-1 gp120 subtype B/subtype E (B/E) proteins demonstrated 31% vaccine efficacy. Here we design an ALVAC/Pentavalent B/E/E/E/E vaccine to increase the diversity of gp120 motifs in the immunogen to elicit a broader antibody response and enhance protection. We find that immunization of rhesus macaques with the pentavalent vaccine results in protection of 55% of pentavalent-vaccine-immunized macaques from simian–human immunodeficiency virus (SHIV) challenge. Systems serology of the antibody responses identifies plasma antibody binding to HIV-infected cells, peak ADCC antibody titres, NK cell-mediated ADCC and antibody-mediated activation of MIP-1β in NK cells as the four immunological parameters that best predict decreased infection risk that are improved by the pentavalent vaccine. Thus inclusion of additional gp120 immunogens to a pox-prime/protein boost regimen can augment antibody responses and enhance protection from a SHIV challenge in rhesus macaques. A previous human HIV-1 vaccine clinical trial, boosting with HIV envelope protein from two strains, demonstrated moderate vaccine efficacy. Here, Bradley et al . show that a pentavalent HIV envelope protein boost improves protection from viral challenge in non-human primates and they identify immune correlates of protection.